If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -14 = 2y + 2 Reorder the terms: -14 + 5y = 2y + 2 Reorder the terms: -14 + 5y = 2 + 2y Solving -14 + 5y = 2 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -14 + 5y + -2y = 2 + 2y + -2y Combine like terms: 5y + -2y = 3y -14 + 3y = 2 + 2y + -2y Combine like terms: 2y + -2y = 0 -14 + 3y = 2 + 0 -14 + 3y = 2 Add '14' to each side of the equation. -14 + 14 + 3y = 2 + 14 Combine like terms: -14 + 14 = 0 0 + 3y = 2 + 14 3y = 2 + 14 Combine like terms: 2 + 14 = 16 3y = 16 Divide each side by '3'. y = 5.333333333 Simplifying y = 5.333333333
| 2x-9=-5 | | 30+5k=-6(4k-8) | | 4(x-8)+2x=18 | | -t/5=15 | | 11x-14=6x+21 | | 15/2h-14/2h | | 45=3y+15 | | 6x^2-21x+18=0 | | (k+9)4=9k+44 | | -2x+10=6 | | h=69.089+2.238F | | 3+n/5=14 | | 3(-4)+7=(-4)-1 | | 7y-1=15 | | 2/5y-8=0-3/5y | | 2(-4)+y=1 | | 12x-4x=180 | | 6-2y=14 | | 3+3x=-6 | | xy+x+zy+z=0 | | 7t=112 | | 3y+15=-16 | | 42j+18-19j=-24 | | 5x+15y+ax+3ay=0 | | 8y-y=7 | | 5(2x+5)=2(4x+11) | | (-7n+3)-(-6n+6)= | | 8=2(2x-5) | | 49-3b=36 | | 8(2x-9)=45 | | 6+0.25x=0.8x-5 | | 6+11x=96 |